Implikasi Berlakunya Protokol Kyoto 1997 terhadap Indonesia - Triatmodjo, Marsudi (Indonesian Journal of International Law, 2005)
The 1997 Kyoto Protocol to the United Nations Framework Convention on Climate Change will entry into force in February 2005. The purpose of this protocol is to stabilize the green house effect concentration in the ozone layer to unharmed level for earth’s climate system. This protocol has a great influence to the developed countries that have a lot of contributions to emission of dangerous gas. Indonesia, as an agricultural country, as well as an archipelagic state, will get the effect of the climate change that have a bad influence to the water recycle and food production. Accordingly, this article will discuss about the implication of the Kyoto Protocol to Indonesia.